Blind willow, sleeping woman - Murakami, Haruki (Vintage Books, 2007)
Here are animated crows, a criminal monkey, an ice man, as well as the dreams that shape us and the things we wish for. Whether during a chance reunion in Italy, a romantic exile in Greece, a holiday in Hawaii or in the grip of everyday life, Murakami's characters confront loss, or sexuality, or the glow of a firefly, or the impossible distance between those who ought to be closest of all.